Jacques Daviel – the inventor of the extracapsular cataract extraction surgery - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
On April 8, 1747, Jacques Daviel called to operate on M. Garion, a master wigmaker, whose cataracts appeared very favorable for surgery. Nevertheless, the expert Daviel was unable to depress lens. At that moment, he decided on a deliberate extraction. After widely opening the right cornea, he passed a small spatula through the pupil and extracted from the posterior chamber the lens. Thus was initiated the first significant advance in cataract surgery since the invention of couching in ancient India.